Repeated-value simplex designs - better rotations of the classical simplex experimental design. (24th May 2022) - Colannino, Joseph
Classical simplex designs allow the assessment of n factors in n + 1 experimental runs. However, the classical design specifies levels, intervals, and coded values that differ from factor to factor, and this is experimentally inconvenient. This research note presents the means to rotate the simplex to orient all factors to the same three coded values p, q, r , or to ±1 if n = 2 J - 1, where J is an integer. Such rotations render the simplex design much more convenient for experimental work. This note also presents a means for generating two-value simplex matrices that may be viewed as non-orthogonal fractions of two-level factorial designs.